Martin, Luther H. and Donald Wiebe (eds) 2017. Religion Explained? The Cognitive Science of Religion after Twenty-five Years - Sutherland, Liam M. (Fieldwork in Religion, 2020)
Martin, Luther H. and Donald Wiebe (eds) 2017. Religion Explained? The Cognitive Science of Religion after Twenty-five Years. xi + 260 pp. London: Bloomsbury. ISBN: 978-1 350-03246-0 £85.00 (hbk); 978-13501-0592-8 £28.99 (pbk); 978-13500-3247-7 £31.30 (e book).